Solutions of systems of nonlinear difference equations that are continuous and bounded on the entire real axis and their properties - Pelyukh, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
For a system of nonlinear difference equations, we establish conditions for the existence and uniqueness of a solution bounded on the entire real axis and study its properties.